Relative Expression of Soluble tnf Versus Transmembrane tnf in Spondyloarthritis - Huriatul Masdar (Jurnal Ilmu Kedokteran, 2010)
TNF is important in rheumatoid arthritis (RA) and spondyloarthritis (SpA) pathogenesis. Recently reports showedsTNF levels were significantly lower in SpA than RA synovial fluid (SF). Therefore, the differential regulation of TNFin both diseases were investigated focusing on the balance of sTNF-tmTNF and both TNF receptors expression. Synovialfluid from 22 RA and 25 SpA were analyzed by ELISA. sTNF was confirmed significantly higher in RA than SpA.Total TNF of synovial tissues assessed by qPCR showed similar levels, suggesting a higher tmTNF/sTNF ratio in SpA.The levels of sTNF-R1 and sTNF-R2 were significantly lower in SpA than RA SF. Interestingly, sTNF-R2/sTNF-R1increased in SpA. qPCR on synovial tissue showed similar mRNA levels for TNF-R2 but decrease of TNF-R1 in SpA.IL-6R levels did not showed differences and TIMP-3 tended to be higher in RA than in SpA SF. In conclusion, weobserved a shift from sTNF/TNF-R1 in RA to tmTNF/TNF-R2 in SpA.